The Investigation of Use as Aggregate in Lightweight Concrete Production of Boron Wastes - Abudalrhman Aldakshe; Hakan Çağlar; Arzu Çağlar; Çağrı Avan (Salehan Institute of Higher Education, 2020)
Lightweight concrete manufacture has been aimed as a result of the use of boron waste which is aggregate of pumice, one of our natural resources, and a valuable industrial waste as a substitution material in different proportions (1%, 3%, 5%, 7%, and 9%). As a result of the study, it was aimed to obtain a water-resistant and lighter material which has higher properties than lightweight concrete in terms of physical and mechanical. The study was carried out as three stages. At the first stage, 90% of the pumice aggregate and 10% of the sand (Reference sample) were used and lightweight concrete was produced. At the second stage, boron waste at the rate of 1%, 3%, 5%, 7%, and 9% was used for pumice aggregate and the doped lightweight concrete sample was produced. At the last stage, tests were carried out for the determination of the physical and mechanical properties of lightweight concrete samples which were produced. For determination of mechanical properties, tensile splitting strength and compressive strength tests were performed. Additionally, specific gravity, water saturated unit volume weight, porosity, and capillary water absorption tests were made for the determination of physical diversities. It was found that the physical and mechanical properties of the material improved with the increase of boron waste in the consequence of this study. The best result was obtained with the boron waste substitution at the rate of 9%. Environmentally harmful boron wastes being used in the construction sector will contribute to sustainability by recycling the boron wastes.